A Pedagogue's Progress, the Cunningham Turn, and the Birth of Creator Studies. (February 2022) - Craig, David
As partners in an ongoing global research initiative over the past 6 years, Queensland University of Technology Distinguished Professor Stuart Cunningham and University of Southern California Clinical Professor David Craig mapped the rise of two competing communication and media industries, Social Media Entertainment and Wanghong. Alongside other vanguard scholars, Cunningham and Craig identified and framed the emergence of Creator Studies, an interdisciplinary field of studies focused on the dynamics of new forms of cultural production across social media platforms from diverse fields, methods, and epistemologies. These developments are described within a picaresque auto-ethnographic account of Cunningham's influence on the author's progression from Hollywood producer to scholar and pedagogue.